ChemInform Abstract: [4 + 2] Annulation of Vinyl Ketones Initiated by a Phosphine‐Catalyzed Aza‐Rauhut—Currier Reaction: A Practical Access to Densely Functionalized Tetrahydropyridines. Issue 3 (22nd January 2013) - Shi, Zugui; Tong, Qinjie; Leong, Wendy Wen Yi; Zhong, Guofu
Abstract In the presence of catalytic amounts of PPh3 and p‐methoxyphenol, N‐sulfonyl‐1‐aza‐1, 3‐dienes undergo the title reaction with vinyl ketones to give the isolated pyridine derivatives exclusively as trans‐isomers.